PRIORITY DIRECTIONS OF DEVELOPMENT OF HOUSING AND COMMUNAL SERVICES - E. B. Atuyeva; H. M. Dusilaeva; M. M. Shabanova (Вестник Дагестанского государственного технического университета: Технические науки)
The modernization of the Russian economy is impossible without a systematic approach to the development of a modern infrastructure of housing and communal services. This requires the adoption of measures to improve the efficiency of the housing stock, the modernization of municipal infrastructure, improve the quality and reliability of delivery of municipal resources, introduction of modern technologies. Problems of housing and communal services are particularly relevant for urban areas - areas of cities and towns where there is an extensive network of engineering infrastructure. The analysis of development of the municipality "City of Makhachkala" showed that although the municipal administration carried out serious work on the development of housing and communal services, today in the field of city life is still a lot of unsolved problems.The package of measures, directed on improvement and further development of the housing-and-municipal sphere is developed.